Synthesis and evaluation of 2-ethynyl-adenosine-5′-triphosphate as a chemical reporter for protein AMPylation1. Issue 31 (21st August 2015) - Creech, Christa; Kanaujia, Mukul; Causey, Corey P.
<x xml:space="preserve">Abstract</x> 2-Ethynyl-adenosine-5′-triphosphate is a chemical reporter for AMPylation that enables visualization of modified protein substrates.